2006
DOI: 10.1016/j.ijsolstr.2005.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of a self-piercing riveted connection under quasi-static loading conditions

Abstract: The behaviour of a self-piercing riveted connection was investigated experimentally and numerically. An extensive experimental programme was conducted on elementary riveted joints in aluminium alloy AA6060 in two different tempers, T4 and T6. The experimental programme was focused on the influence of important model parameters such as thickness of the plates, geometry of the specimens, material properties of the plates and loading conditions. An accurate 3D numerical model of different types of riveted connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 5 publications
5
59
1
1
Order By: Relevance
“…Accordingly, a higher strength was expected. The observed deformation and failure modes of the SPR connections were in accordance with the observations of Porcaro et al (2006a).…”
Section: Single Connector Testssupporting
confidence: 88%
See 1 more Smart Citation
“…Accordingly, a higher strength was expected. The observed deformation and failure modes of the SPR connections were in accordance with the observations of Porcaro et al (2006a).…”
Section: Single Connector Testssupporting
confidence: 88%
“…The shear, tensile and combined shear and tensile quasi-static load responses of SPR connections between aluminium extrusions were investigated by Porcaro et al (2006a). They also studied the influence of the plate thickness, rivet geometry, material properties and loading conditions (Porcaro et al, 2006b), and conducted dynamic tests to assess the rate effect on the behaviour of SPR connections (Porcaro et al, 2008).…”
Section: Even Though Little Information About Fds Connections Is Founmentioning
confidence: 99%
“…This model was based on the post-process geometry, figure 7a, and corresponding material properties obtained from the riveting process [5]. The 3D model is divided into two sub-groups: the internal part and the external part.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Voelkner [13] suggested that the overall thickness of the connected sheets shall not be greater than 6 mm for SPR connections. Parameter analysis of SPR connections under different combinations of sheet materials was presented in Porcaro et al [14,15], their results suggested that thickness and material properties of sheets had significant influence on the shear strength. Li and Han [16,17] concluded that the edge distance had effect on dynamic fatigue strength and static behavior of SPR aluminum joints.…”
Section: Introductionmentioning
confidence: 99%